2018
DOI: 10.1155/2018/5978293
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in a Four-Generation Family with Aniridia Carrying a NovelPAX6Mutation

Abstract: Aniridia is a congenital disease that affects almost all eye structures and is primarily caused by loss-of-function mutations in the PAX6 gene. The degree of vision loss in aniridia varies and is dependent on the extent of foveal, iris, and optic nerve hypoplasia and the presence of glaucoma, cataracts, and corneal opacification. Here, we describe a 4-generation family in which 7 individuals across 2 generations carry a novel disease-causing frameshift mutation (NM_000280.4(PAX6):c.565TC>T) in PAX6. This mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Notably, mutations in Pax6 are more typically associated with aniridia, a panocular congenital disease characterized by foveal hypoplasia, optic nerve hypoplasia, limbal stem cell deficiency, and varying degrees of iris hypoplasia (reviewed in Lim et al, 2017 ; Sannan et al, 2017 ; Syrimis et al, 2018 ; Wawrocka and Krawczynski, 2018 ; Lima Cunha et al, 2019 ; Lee et al, 2020 ; Tripathy and Salini, 2020 ). However, phenotypic variation of the same Pax6 gene mutation has shown both aniridia and PA within one family ( Wang et al, 2018 ), and PA has been associated with aniridia in more than 10% of cases ( Dolezal et al, 2019 ).…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%
“…Notably, mutations in Pax6 are more typically associated with aniridia, a panocular congenital disease characterized by foveal hypoplasia, optic nerve hypoplasia, limbal stem cell deficiency, and varying degrees of iris hypoplasia (reviewed in Lim et al, 2017 ; Sannan et al, 2017 ; Syrimis et al, 2018 ; Wawrocka and Krawczynski, 2018 ; Lima Cunha et al, 2019 ; Lee et al, 2020 ; Tripathy and Salini, 2020 ). However, phenotypic variation of the same Pax6 gene mutation has shown both aniridia and PA within one family ( Wang et al, 2018 ), and PA has been associated with aniridia in more than 10% of cases ( Dolezal et al, 2019 ).…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%
“…Twelve patients were members of a previously described 4-generation family, in which genetic testing on generations iii, and iv showed a splice-site mutation (c.565TC > T) in PAX6 (NM_000280.4) [ 27 ]. Seven additional patients were related to this family by marriage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the submitted variants involve nonsense or frameshift pathogenic variants resulting in premature termination codons and haploinsufficiency [ 85 , 86 ] and these represent 75–80% of aniridia cases. Numerous studies have described PAX6 pathogenic variants as resulting in a complete penetrance of aniridic ocular changes; however, single pathogenic variants result in a wide variety and severity of phenotypes [ 90 , 91 ]. Some reports have suggested that the level of disease severity is possibly correlated with the level of PAX6 expression with loss of function pathogenic variants resulting in the most severe cases [ 86 ].…”
Section: Syndromesmentioning
confidence: 99%
“…Some reports have suggested that the level of disease severity is possibly correlated with the level of PAX6 expression with loss of function pathogenic variants resulting in the most severe cases [ 86 ]. Still, this does not explain the varying severity and onset of pathology amongst family members with identical pathogenic variants [ 90 ]. Compound heterozygous pathogenic variants in PAX6 are thought to be lethal; however, studies have described such patients with mortality in late gestation or shortly after birth with severe craniofacial and ocular malformations [ 85 ].…”
Section: Syndromesmentioning
confidence: 99%